SECRET SERVICES, 1918-1939 their development in britain, germany, and russia. - ANDREW SANGSTER, AUTHOR (CAMBRIDGE SCHOLARS PUBLIS, 2020)
This book examines the nature of the secret services and the role of the secret police in Britain, Russia, and Germany during the interwar years. It traces the growth of the secret services and police in these countries, indicating how they differed in their development. The SIS (MI6), MI5 and Special Branch in England appeared more like a Gentleman's Club from Eton and Oxbridge, especially when compared to the German Gestapo, SS-SD, and Abwehr in Germany, and the Cheka, GPU, NKVD and KGB in Stalinist Russia. The British were short of money and resources, while the Germans were interested in e.